2013
DOI: 10.2106/jbjs.l.01122
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome Following Carpal Wedge Osteotomy in the Arthrogrypotic Patient

Abstract: Long-term outcomes reveal that surgical correction of wrist flexion posture in children with amyoplasia congenita results in improvement that is sustained over time. The surveys and questionnaires completed by parents or guardians indicated that they were satisfied with the results of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Twelve articles that met all inclusion and exclusion criteria were included, [1,[5][6][7][8]10,[14][15][16][17][18][19] and all included articles were published as Level 4 evidence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve articles that met all inclusion and exclusion criteria were included, [1,[5][6][7][8]10,[14][15][16][17][18][19] and all included articles were published as Level 4 evidence.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Foy et al, 13 patients required additional surgery (thenar slides, tricepsplasty, elbow release) but no other complications were noted [10]. Both reviews concluded that dorsal wedge osteotomy is capable of correcting wrist flexion deformity and maintained results over time [8,10,22].…”
Section: Wristmentioning
confidence: 99%
See 3 more Smart Citations